Detection of Human Papillomavirus, p53 and c-erbB-2 Protein Expression in Juvenile Laryngeal Papillomatosis: A Report of 2 Cases - Siti Aishah Md Ali,; Ilina Isahak,; Dahlan Sabil,; Lokman Saim,; Fatimah Sahlan,; Abdullah Sani Mohamed, (Penerbit UKM, 2006)
The association of human papillomavirus (HPV) with juvenile laryngeal papillomatosis has been well documented. We report two cases of juvenile laryngeal papillomatosis and correlated these cases with presence of HPV, p53 and c-erbB-2 proteins. The first case was a one-year-old male patient and the second a six-year-old female patient. Formalin-fixed paraffin-embedded biopsy specimens were tested for the presence of HPV genome by the technique of in situ hybridisation using wide spectrum and type specific biotinylated probes while the immunohistochemical expression of p53 (D07, 1:50) and c-erbB-2 (DAKO A0485, 1:300) proteins were evaluated with commercially available antibodies. Histologically the tumours in both cases showed papillary configuration of squamous papilloma. The first case detected HPV type 6, HPV type 11 and p53 protein expression while the second case showed only HPV type 6. Both cases of HPV showed positive signals confined to the nuclei in the superficial squamous epithelium. The first case showed p53 positivity seen from the basal region up to one third of the epithelium of laryngeal papillomas and the subsequent recent repeat biopsy showed the positivity of p53 had extended throughout the upper layers of the epithelium. Expression of c-erbB-2 protein was not detected in both cases. These findings were similar as in other studies where follow-up of the cases was recommended since they tend to recur